2018
DOI: 10.3389/fnmol.2018.00109
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Autophagy by a Small Molecule Inverse Agonist of ERRα Is Neuroprotective

Abstract: Mechanistic insights into aggrephagy, a selective basal autophagy process to clear misfolded protein aggregates, are lacking. Here, we report and describe the role of Estrogen Related Receptor α (ERRα, HUGO Gene Nomenclature ESRRA), new molecular player of aggrephagy, in keeping autophagy flux in check by inhibiting autophagosome formation. A screen for small molecule modulators for aggrephagy identified ERRα inverse agonist XCT 790, that cleared α-synuclein aggregates in an autophagy dependent, but mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Further understanding of the mechanisms for α‐synuclein‐autophagy crosstalk in PD might have crucial therapeutic applications. Backing this notion, both in vitro and in vivo studies show that enhancing autophagy and autophagosome‐lysosome fusion could ameliorate PD‐like features by clearing aggregated α‐synuclein (Suresh et al ; Suresh et al ).…”
Section: Autophagy In Pd; Cause and Effect Hand In Handmentioning
confidence: 99%
See 1 more Smart Citation
“…Further understanding of the mechanisms for α‐synuclein‐autophagy crosstalk in PD might have crucial therapeutic applications. Backing this notion, both in vitro and in vivo studies show that enhancing autophagy and autophagosome‐lysosome fusion could ameliorate PD‐like features by clearing aggregated α‐synuclein (Suresh et al ; Suresh et al ).…”
Section: Autophagy In Pd; Cause and Effect Hand In Handmentioning
confidence: 99%
“…Over-expression of a-synuclein also directly compromises macroautophagy through inhibition of Rab1a (Winslow et al 2010). It is also pertinent to note that aggregated a-synuclein in the soma is a key target of treatment strategies in development through induction of macroautophagy (Suresh et al 2017;Suresh et al 2018a).…”
Section: Pink1 and Parkin: Role In Mitophagy And Beyondmentioning
confidence: 99%
“…Several mTOR-independent modifiers of autophagy are gaining interest as therapeutics, with AMPK activating molecules such as trehalose and metformin proving effective in reducing neurodegenerative phenotypes in models of AD [168, 169], ALS [170172], HD [173, 174] and tauopathies [175]. Cellular targets not directly associated with the core autophagy machinery have also been found to modify neurodegeneration, including Estrogen Related Receptor α [176] and cAMP [177, 178]. Interestingly, the widely used AD-therapeutic memantine has emerged from a screen of clinically approved molecules which enhance autophagy [179], suggesting a potential mode of action for the drug which may be repurposed in other neurodegenerative disorders.…”
Section: Autophagymentioning
confidence: 99%
“…In PD, the continuous aggregate formation leads to an intracellular defect wherein proteostasis regulating mechanisms such as chaperones, Ubiquitin Proteasome System (UPS) and macroautophagy (henceforth autophagy) are impaired, leading to neuronal death [5]. Proof-of-principle experiments have demonstrated that clearing α-synuclein aggregates is beneficial and cytoprotective [6], [7], [8]. Toxic protein oligomers and aggregates are considered to be the substrates for autophagy machinery due to their size [9].…”
Section: Introductionmentioning
confidence: 99%